Exploring the role of industry associations and regulators: Reconstructing corporate governance and sustainability reporting - Wiyarni, Wiyarni; Amin, Aminul; Kadarusman, Kadarusman (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the role of industry associations and regulators in reconstructing corporate governance and sustainability reporting. This study employs both quantitative and qualitative approaches. The quantitative approach utilizes the Partial Least Squares (PLS) method with the SmartPLS program to test the influence of corporate governance on sustainability reporting through industry associations and regulators. The testing was conducted on 228 manufacturing companies, 105 financial institutions, and 30 hotels and restaurants listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Corporate governance is measured by the number of meetings held by the board of directors, board of commissioners, and audit committee. Industry associations are measured by the number of meetings. Regulators are measured using a dummy variable, with companies’ sustainability reports in accordance with SEOJK 16/2021 assigned a value of 1, and those not reporting assigned a value of 0. Sustainability reports are measured using the Sustainability Report Disclosure Index (SRDI) based on the 2021 GRI Standards. The results indicate that industry associations and regulators play a mediating role in the relationship between corporate governance and sustainability reporting. These findings are further supported by qualitative approaches, including in-depth interviews and focus group discussions with industry associations and regulators.